Why I Don't Write Children's Literature - Soto, Gary (Book collections on Project MUSE., 2015)
"Gary Soto is a poet and, in a previous writing life, an author of children's literature. Moreover, he is an essayist whose works have been celebrated for their openness and vivid image-making. In this volume, the poet again offers prose that is robust, confessional, and peculiar in its observations. Soto's world is quirky, here captured in a series of bite-sized narratives full of humor and insight. He befriends daffodils, praises theater and tribute bands, and snuggles up with his wife of almost forty years. Like many boomers, he laments his sense of failure. LIke them, he shrugs off that failure to recast his remaining years"--Back cover.